2000
DOI: 10.1200/jco.2000.18.13.2537
|View full text |Cite
|
Sign up to set email alerts
|

Southwest Oncology Group Study of Paclitaxel and Carboplatin for Advanced Transitional-Cell Carcinoma: The Importance of Survival as a Clinical Trial End Point

Abstract: The combination of paclitaxel and carboplatin for the treatment of advanced TCC is reasonably well tolerated. However, a response proportion considerably lower than that previously reported was noted. In addition, the median survival time of 9 months was less than the survival time previously reported for patients treated with the combination of methotrexate, vinblastine, doxorubicin, and cisplatin. Although our results may reflect enrollment of patients with poor prognostic features, they also call into quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(26 citation statements)
references
References 20 publications
3
21
1
1
Order By: Relevance
“…9,10,12 Poor prognostic risk factors in advanced urothelial carcinoma have been previously identified. In a recent study by Bajorin et al of 203 patients with advanced bladder carcinoma treated with M-VAC, the presence of lung, liver, or bone metastases and a baseline Karnofsky performance status less than 80% predicted independently for a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10,12 Poor prognostic risk factors in advanced urothelial carcinoma have been previously identified. In a recent study by Bajorin et al of 203 patients with advanced bladder carcinoma treated with M-VAC, the presence of lung, liver, or bone metastases and a baseline Karnofsky performance status less than 80% predicted independently for a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, a response rate of only 21% was seen, with median survival of 9 months. 12 Both studies by Pycha and SWOG required a creatinine clearance Ն 30 mL/ minutes for enrollment. The authors of the SWOG trial have suggested that differences in response rates in these trials may be linked to different patient characteristics, for example, the relative balance of patients with node only metastases versus visceral metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, those patients had a median survival of 9 months, similar to the survival observed in previous studies with the same regimen. 31 In another recently published study 32 that included 17 patients with poor prognostic features, carboplatin plus gemcitabine produced an overall response rate of 58.8%, a median time to disease progression of 4.6 months, and a median overall survival of 10.5 months. WHO Grade 3-4 granulocytopenia and thrombocytopenia were reported in 70% of patients and 47% of patients, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The objective has been to find combinations that demonstrate improved efficacy and a better toxicity profile compared with that of M-VAC. The most extensively studied drugs have been gemcitabine (Moore et al, 1999;Von der Maase et al, 1999;Kaufman et al, 2000) and paclitaxel (Redman et al, 1998;Vaughn et al, 1998;Zielinski et al, 1998;Dreicer et al, 2000;Small et al, 2000), each in combination with cisplatin or carboplatin. These studies have usually shown an elevated activity with a favourable toxicity profile (Table 3).…”
Section: Discussionmentioning
confidence: 99%